2021
DOI: 10.1080/21655979.2021.2005875
|View full text |Cite
|
Sign up to set email alerts
|

Serum hsa_circ_0087776 as a new oncologic marker for the joint diagnosis of multiple myeloma

Abstract: Multiple myeloma (MM) is a hematologic malignancy caused by abnormal proliferation of bone marrow plasma cells, which lacks diagnostic markers and has a general prognosis. At present, the understanding of its pathogenesis provides the basis for the combined diagnosis and new targeted therapy of the disease. In this study, quantitative real-time PCR was used to detect 136 MM patients and 74 healthy controls, and the clinical application value of hsa_circ_0087776 as a new tumor marker and combined diagnosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Several tumor markers for combined diagnosis might be an optimized selection for the accurate diagnosis of MM. Gong et al ( Gong et al, 2021 ) discovered that circ_0087776 expression was significantly lower in serum of 136 MM patients compared with 74 healthy controls, with the consistent result in MM cells. Importantly, it significantly increased the sensitivity with ALB, β₂-MG joint diagnosis, emphasizing that it could be used as a new biomarker for combined diagnosis of MM ( Gong et al, 2021 ).…”
Section: Circrnas In MMmentioning
confidence: 74%
See 3 more Smart Citations
“…Several tumor markers for combined diagnosis might be an optimized selection for the accurate diagnosis of MM. Gong et al ( Gong et al, 2021 ) discovered that circ_0087776 expression was significantly lower in serum of 136 MM patients compared with 74 healthy controls, with the consistent result in MM cells. Importantly, it significantly increased the sensitivity with ALB, β₂-MG joint diagnosis, emphasizing that it could be used as a new biomarker for combined diagnosis of MM ( Gong et al, 2021 ).…”
Section: Circrnas In MMmentioning
confidence: 74%
“…Gong et al ( Gong et al, 2021 ) discovered that circ_0087776 expression was significantly lower in serum of 136 MM patients compared with 74 healthy controls, with the consistent result in MM cells. Importantly, it significantly increased the sensitivity with ALB, β₂-MG joint diagnosis, emphasizing that it could be used as a new biomarker for combined diagnosis of MM ( Gong et al, 2021 ). Altogether, these results verify certain circRNAs as diagnostic and prognostic biomarkers in MM, and further cohort studies are needed to explore more effective biomarkers in the future.…”
Section: Circrnas In MMmentioning
confidence: 74%
See 2 more Smart Citations
“…First, our study did not include enough clinical samples, and there was a lack of relevant follow-up prognostic information, which made it difficult for us to analyze the correlation between circPOLR2A expression and cRCC prognosis. Due to the stability of circRNAs endowed by their loop structure, several studies have demonstrated the clinical application potential of circRNAs as cancer biomarkers [77,[82][83][84]. Hence, including more cRCC samples with sufficient follow-up data is necessary for evaluating the clinical value of circPOLR2A in future research, which is of great significance for subsequent clinical transformation.…”
Section: Discussionmentioning
confidence: 99%